THE FINE STRUCTURE OF THE VENTRAL INTERSEGMENTAL ABDOMINAL MUSCLES OF THE INSECT RHODNIUS PROLIXUS DURING THE MOLTING CYCLE : I. Muscle Structure at Molting - Toselli, Paul A. (The Rockefeller University Press, 1968)
Rhodnius prolixus, a South American insect, molts five times in its development to an adult after emerging from the egg. Each molting cycle is triggered with a blood-meal. The ventral intersegmental abdominal muscles of Rhodnius develop during each molting cycle and are functional at molting. The fine structure of these fully developed muscles from fourth stage larval insects is studied. They have the characteristic structure of slow muscles. They have multiple motor nerve endings, and the myofibrils are poorly defined in cross-section. Longitudinal sections show long sarcomeres (8–10 µ), irregular Z-lines, and no apparent H zones. No M line is seen. Transverse sections through the A-band region show that each hexagonally arranged thick filament is surrounded by 12 thin filaments. Two thin filaments are shared by two neighboring thick filaments. The ratio of thin to thick filaments is 6:1. This structure is related to that found in vertebrate skeletal muscle and insect flight muscle.